2003
DOI: 10.1046/j.1468-2982.2003.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Dural Protein Extravasation Induced by Meta-Chlorophenylpiperazine (Mcpp) Involves Nitric Oxide and 5-HT2B Receptor Activation

Abstract: The compound m-chlorophenylpiperazine (mCPP), which is known to trigger migraine-like head pain in some subjects, was evaluated for its ability to induce dural plasma protein extravasation (PPE) in guinea pigs. Intravenous mCPP dose-dependently increased PPE. This effect was inhibited by non-selective 5-HT2 receptor antagonists (methysergide, LY53857, LY215840), by a peripherally restricted 5-HT2 receptor antagonist (xylamidine) and by a 5-HT2B selective receptor antagonist (LY202146). These data suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
3
38
0
1
Order By: Relevance
“…In conclusion, our study shows for the first time that peripheral 5-HT 2B R activation can both prevent and cure CCI-induced neuropathic pain, whereas previous studies have reported opposite findings in other pain models, such as migraine [29,50,51] and visceral pain [45,47]. In these cases, the etiology of pain is quite different from that of neuropathic pain.…”
mentioning
confidence: 44%
“…In conclusion, our study shows for the first time that peripheral 5-HT 2B R activation can both prevent and cure CCI-induced neuropathic pain, whereas previous studies have reported opposite findings in other pain models, such as migraine [29,50,51] and visceral pain [45,47]. In these cases, the etiology of pain is quite different from that of neuropathic pain.…”
mentioning
confidence: 44%
“…21 Moreover, NO in guinea-pig dura mater induces extravasation and other changes similar to those induced by neurogenic inflammation. 22 Interestingly, in humans, GTN has been reported to induce: 1) a much more pronounced dilatation in the superficial temporal artery than in the radial artery 23 ; 2) a potent vasodilatation in veins throughout the body, including the head; 3) a marked increase in cerebral blood volume, probably because of cerebral venous dilatation 6 ; and 4) no effect on regional cerebral blood flow.…”
Section: Effect Of No In the Cerebral And Extracerebral Circulationsmentioning
confidence: 99%
“…Indeed, 5-HT 2B receptor mRNA has been demonstrated in human coronary artery (Ishida et al 1999), and activation of 5-HT 2B receptors in human coronary artery induces NO release (Ishida et al 1998). Selective 5-HT 2B receptor antagonists have been described (Forbes et al 1995;Johnson et al 2003) and proven efficacious in blocking plasma protein extravasation . In addition, 8′-hydroxy-dihydroergotamine, the major metabolite of the antimigraine drug dihydroergotamine, may induce a persistent desensitization of 5-HT 2B receptors, which may contribute to its therapeutic efficacy (Schaerlinger et al 2003).…”
Section: -Ht 2 Receptor Subtypesmentioning
confidence: 99%